Assessment Sleep Pattern among Patients undergoing Hemodialysis in Al-Diwaniyah Teaching Hospital - Ismael Mohammed Alsaadi; Haider Abbas Hadi Al-Mhanaa; Widad Abd Aljabbar Mozzan; Fatima Kamil Salman; Saad Mardi Muhammad; Rusul Mushtaq Talib (Journal of Biomedicine and Biochemistry, 2026)
Background: Kidney failure is a condition in which one or both of the kidneys can no longer work on their own. Sometimes, kidney failure is temporary and comes on quickly. Other times, it is a chronic condition that can get worse slowly over a long time. Objectives: The aims of the existing study were to identify sleep patterns for patients undergoing hemodialysis and to find out the association between sleep patterns for patients undergoing hemodialysis and their socio demographic variables.Methodology: A descriptive cross-sectional study was conducted in in Al-Diwaniyah Teaching Hospital. Data were collected from (15 January to 15 February 2024) through the self-report questionnaire and analyzed through the descriptive and inferential statistical (SPSS) method. Results: The study revealed that hemodialysis patients are predominantly middle-aged males, with many reporting poor sleep qualities, including daytime dysfunction, insufficient restoration after sleep, and difficulties falling or staying asleep. Despite these challenges, most patients expressed general satisfaction with their sleep pattern but experienced disruptions, such as noise and waking during sleep. The findings highlight the need for targeted interventions to improve sleep quality and overall health in this population.Conclusions: 60% of participants were classified as having low overall sleep quality. This underscores the widespread nature of sleep disturbances within the hemodialysis population and highlights the critical need for targeted interventions to improve sleep quality, which may in turn enhance patients' overall health and well-being. Recommendations: Given the widespread impact of poor sleep on daily functioning, further clinical attention should be given to improving sleep hygiene, minimizing nocturnal disruptions, and addressing underlying health issues that contribute to poor sleep quality in hemodialysis patients.